Сooperation between kazakhstan and the united states in ensuring regional security (International relations and international law Journal, 2016)
The United States has important strategic interests in promoting regional cooperation, resolution of border conflicts, fighting against terrorism and resolving the Afghan crisis and plays an important role in stabilizing Central Asian region. Nowadays the United States attaches great importance to ensuring security and regional integration in Central Asia through the promoting of various initiatives. Thus, “New Silk Road” project which was proposed by the United States provides for building of an integrated economic space between Central Asia and South Asia where Afghanistan will be key binding unit. The article examines the U.S. policy in Central Asia and its impact on the bilateral cooperation between Kazakhstan and the United States in the ensuring regional security
Keywords: Kazakh-American relations; «New Silk Road» project; regional security; military cooperation